CONSUMER'S SATISFACTION - EXPLANATORY MODELS - Margarita Tejera Gil; Santiago Rodriguez Feijoó; Alejandro Rodriguez Caro; Delia Davila Quintana (European Regional Science Association (ERSA), 2005)
When the first studies related to consumer satisfaction began to appear in the sixties, nobody could imagine protagonism that it would reach with the course of the time. Nowadays not only private sector companies dedicate part from their resources to the study of the degree of satisfaction of their clients, but satisfaction studies are more and more increasing preoccupation in the state sector, therefore works related to the satisfaction of the patients, the contributors or with the tourist destiny can be found. Firstly, a revision of the different models that have been used to explain customer satisfaction level is presented, using the cognitive and the affective-cognitive models. In the first case, human being is looking as a rational being that can process information about the different attributes of the services to form his personal satisfaction. The most useful model within this category is the expectation disconfirmation model. These kind of models explain satisfaction as a function of the degree and direction of the discrepancy between expectation and perceptions. It has evolved all over time resulting in a lot of different approaches. We have also studied the equity model, in which consumer does a benefit-cost analysis not only its owns but from the rest of people who take part in the transaction. Finally, in the affective-cognitive models, human being is seeing like a complex being that is not solely an information processor but experiences feelings and emotions that also influence in their judgments of satisfaction. Secondly, it has been realized an empirical application in which we have used the main variables in the expectation disconfirmation model: perceptions, expectations and discrepancies to estimate some logit models. The tourists who visit Tenerife are classified as satisfied or unsatisfied. Then, we model the probability of each characteristic using tourist's scores on some destination attributes. Two samples have been used. The first one was obtained at the time of arriving; the second one has been made when leaving the island. Since tourists are not necessary the same in both samples, a statistic inference process has been made to use all the information available. The best model is obtained when expectations and perceptions are used at the same time, so we obtain a 75% of right classification. To sum up, we have found that perceptions are the main subject for the tourist's satisfaction, although we can't forget the importance of expectations to complete the model.
Keywords: 330